Effectiveness of mepolizumab for eosinophilic pneumonia following bronchial thermoplasty. Issue 2 (18th December 2019) - Otoshi, Ryota; Baba, Tomohisa; Komatsu, Shigeru; Asaoka, Masato; Hagiwara, Eri; Ogura, Takashi
Abstract : A 57‐year‐old woman with poorly controlled diabetes was admitted to our hospital for additional treatment of severe asthma. Although bronchial thermoplasty was performed in the both upper lobes, cough and dyspnoea gradually appeared 2 weeks later. High‐resolution computed tomography revealed thickness of intralobular septa and a diffuse ground‐glass attenuation in the lung fields. Laboratory examination revealed elevated levels of serum eosinophils and total immunoglobulin E. Bronchoalveolar lavage fluid showed a remarkable increase of eosinophils as high as 48.5%, then eosinophilic pneumonia was diagnosed. Although treatment with steroids resulted in an improvement of eosinophilic pneumonia, the treatment was discontinued after 4 days because it worsened her diabetic condition. Since eosinophilic pneumonia recurred after discontinuing steroid, mepolizumab was administered, which subsequently improved her disease condition. Clinicians should be aware that bronchial thermoplasty can lead to eosinophilic pneumonia and mepolizumab might be an effective treatment in this setting. Abstract : Bronchial thermoplasty (BT) is a bronchoscopic procedure for treating severe asthma using thermal energy to reduce airway smooth muscle. There are some reports of complications such as bronchitis and atelectasis due to transient inflammation and oedema, but, to the best of our knowledge, no studies have reported eosinophilic pneumonia (EP) due to BT. Mepolizumab is an anti‐interleukin‐5 monoclonal antibody that is reportedly effective against eosinophilic inflammation such as bronchial asthma; however, only few studies have reported its use in treating EP. Here, we report the effectiveness of mepolizumab in treating EP following BT.